Improving Students’ Vocabulary by Using Crossword Puzzle Games in Eighth Grade SMPN 1 Watang Pulu - Ananda, Rizki Tri; Patahuddin, Patahuddin; Patintingan, Amir (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2023)
Crossword Puzzle Games provides a number of questions or word phrases as a key to fill in a series of blank boxes that are designed in such a way. Crosword Puzzle can be used as a good games and fun learning without losing the essence of learning. The researcher applied a quasi-experimental method in this research. For the population, SMPN 1 Watangpulu has 210 students in eighth grade which is divided into 7 classes. Then, with 27 students in class VIII D as the experimental class and 19 in class VIII C as the control class. The results showed an improvement in the vocabulary mastery of students who used the Crossword Puzzle Games compared to students who used the Word Searches game. This was evidenced by the average score of students before treatment was the experimental class obtained 42.85 and the mean score of class control was 45.26. So, it can be concluded that applied the Crossword Puzzleis an effective to improving students’ vocabulary mastery in Eighth grade of SMPN 1 Watangpulu for the 2021/2022 academic year.